2020
DOI: 10.1002/anie.201914458
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Integer‐Charge Transfer Regime in Molecularly Doped Oligothiophenes by Efficient Decarboxylative Cross‐Coupling

Abstract: A library of symmetrical linear oligothiophene was prepared employing decarboxylative cross‐coupling reaction as the key transformation. Thiophene potassium carboxylate salts were used as cross‐coupling partners without the need of co‐catalyst, base, or additives. This method demonstrates complete chemoselectivity and is a comprehensive greener approach compared to the existing methods. The modularity of this approach is demonstrated with the preparation of discreet oligothiophenes with up to 10 thiophene repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…Interestingly, the recent developments such as the iterative exponential growth (IEG) strategy facilitate an efficient synthetic access to discrete oligomers. 9,10 Over the last few decades, a wide variety of discrete oligomers including oligo((meth)acrylate)s, 11,12 oligo(ethylene imine)s, [13][14][15] oligo(caprolactone)s, [16][17][18] oligo(siloxane)s, [19][20][21][22] oligo(thiophene)s, [23][24][25] and oligo(peptide)s [26][27][28][29] have been investigated. These oligomers aid in discovering length-specific properties, for example, aggregation, folding, host-guest interactions, and light absorption, that are otherwise hidden in polydisperse polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the recent developments such as the iterative exponential growth (IEG) strategy facilitate an efficient synthetic access to discrete oligomers. 9,10 Over the last few decades, a wide variety of discrete oligomers including oligo((meth)acrylate)s, 11,12 oligo(ethylene imine)s, [13][14][15] oligo(caprolactone)s, [16][17][18] oligo(siloxane)s, [19][20][21][22] oligo(thiophene)s, [23][24][25] and oligo(peptide)s [26][27][28][29] have been investigated. These oligomers aid in discovering length-specific properties, for example, aggregation, folding, host-guest interactions, and light absorption, that are otherwise hidden in polydisperse polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[73] Some of the thiophene and furan carboxylic acid starting materials are commercially available (2f and 2g), while others were synthesized according to protocols previously developed (2h, 2i and 2k). [74,75] All carboxylic acids screened are bench stable, non-volatile, and are easily manipulated open to an air atmosphere. This renders them more practical and safer to work with compared to the corresponding organometallic reagents necessary for comparable reactions, such as organotins or Grignard reagents (for further information on the synthesis of starting materials, refer to SIII).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the synthesis of perfluoroaryls was reported via Cu­(I)-supported decarboxylation cross-coupling of fluorobenzoates with aromatic iodides. This synthetic strategy is characterized with less sensitive catalytic compounds, only CO 2 generated as a byproduct, low cost, and high selectivity. , Therefore, it can be applied to replace former traditional, costly, and highly sensitive organopalladium catalytic compounds . Extensive research was reported on the use of organopalladium catalysis in cross-coupling chemistry for the synthesis of fluoroaryls.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research was reported on the use of organopalladium catalysis in cross-coupling chemistry for the synthesis of fluoroaryls. However, it still suffers disadvantages, such as low selectivity, side reactions, low yield, and substantial quantities of byproducts leading to extra purification cost. S N Ar is a vital synthesis method in which a nucleophilic substance substitutes a good departing group, such as fluorine, located on an aryl ring. S N Ar of fluorine by different nucleophiles has been investigated for aryl moieties substituted with electron-deficient moieties, such as polyhalogens and sulfonyl, cyano, and nitro groups. Those electron-deficient groups facilitate faster S N Ar providing higher yields.…”
Section: Introductionmentioning
confidence: 99%